Effective Treatment in Amyotrophic Lateral Sclerosis? Invest in Each Player - Chandawrkar, Akash; Özdinler, P. Hande (İstanbul Kültür Üniversitesi, 2007)
ALS (Amyotrophic lateral sclerosis) is a complex neurodegenerative disorder that affects corticospinal motor neurons in the cortex, corticobrainstem neurons and the spinal motor neurons in the spinal cord. ALS can develop both due to genetic or sporatic causes. The genetic causes of the disease are largerly unknown, but the cellular interactions between motor neurons and their environment are beginning to elicudate insights into the cellular pathogenesis of the disease. Even though cognition, memory and other brain functions are left intact in patient, the severed motor neuron circuitry leaves them paralyzed. To develop therapeutic approaches in ALS, there is a growing need to understand each and every component of the motor neuron circuitry, and their interaction in detail. In this rewiew, we will introduce cellular components of the complex neurocircuitry and discuss their possible contribution for therapeutic approaches in ALS.
Keywords: Amyotrophic Lateral Sclerosis; Neuron; Nöron